KEMAMPUAN PRIMER GENERAL CK4/CK2 VIRUS INFECTIOUS BRONCHITIS (IBV) UNTUK MENGAPLIFIKASI GENOM IBV ISOLAT LAPANG INDONESIA - Dharmayanti, N.L P.I.; Asmara, W.; Artama, W. T.; Indriani, R.; Darminto, Darminto (Perhimpunan Biologi Indonesia, 2002)
ABSTRACTCapability of general primer CK4/CK2 infectious bronchitis virus (IBV) to amplify of genomic IBV field isolates in Indonesia. Avian infectious bronchitis virus (IBV), the prototype of coronaviridae, is highly contangius, economically important pathogen of the chickens. Comparative sequence analysis of IBV S1 gene revealed regions that were conserved among serotypes. Two of conservesd region were used to develop degenarate general primer CK4/CK2 for amplifying IBV genomic RNA by RT-PCR. The aims of this study to demonstrated ability of general primer CK4/CK2 for amplified S1 gene IBV field isolates in Indonesia. The result of this is study suggest that only three IBV field isolates that can be amplified by primer CK4/CK2 that are I-14, I-37 and I-269.Key words: Capability, general primer CK4/CK2, infectious bronchitis virus, field isolates